PENGARUH CORPORATE SOCIAL RESPONSIBILITY (CSR), FINANCIAL DISTRESS, CORPORATE’S GROWTH, DAN FIRM SIZE TERHADAP EARNINGS RESPONSE COEFFICIENT (ERC) - Sakinah, Zevira; Putra, Yudi Partama (Universitas Muhammadiyah Palembang, 2024)
The purpose of this study is to determine the influence of corporate social responsibility (CSR), financial distress, corporate's growth and firm size on earnings response coefficient (ERC). The data analysis method used in this study is a quantitative method and uses panel data regression analysis techniques. The population in this study is manufacturing companies listed on the Indonesia Stock Exchange in 2015-2022. The results show that financial distress has an effect on earnings response coefficient (ERC), corporate social responsibility (CSR), corporate's growth, and firm size has no effect on earnings response coefficient (ERC).